Urban processes, water dynamics and climate change - Jover Biboum, Margarita; García Rubio, Rubén; Ávila Calzada, Carlos (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2021)
Essential to any form of life, water defines our blue planet. Historically, human settlements have managed this resource for both personal use and the development of all kind of activities. Old settlements and their hydrologic systems found at some point in time a balance, but with the industrial revolution, urban development and its relation to water systems and associated ecologies have drastically transformed. Today’s socioecological crisis is unprecedented. Humanity’s capacity for environmental transformation has come to define a new geological era, known as the Anthropocene (the era of men). Understanding the causes of this planetary transformation calls for alternative and more precise names such as Thanatocene (the era of war), Phagocene (the era of consumption), Thermocene (the era of global warming) and Capitalocene (the era of capital).
Keywords: Urban Processes; Water Dynamics; Climate Change